Epigenome-wide association study of dietary fatty acid intake - Julia Lange de Luna; Aayah Nounu; Sonja Neumeyer; Lucy Sinke; Rory Wilson; Fabian Hellbach; Pamela R. Matías-García; Thomas Delerue; Juliane Winkelmann; Annette Peters; Barbara Thorand; Marian Beekman; et al. (Clinical Epigenetics, 2024)
Abstract Background Dietary intake of n-3 polyunsaturated fatty acids (PUFA) may have a protective effect on the development of cardiovascular diseases, diabetes, depression and cancer, while a high intake of n-6 PUFA was often reported to be associated with inflammation-related traits. The effect of PUFAs on health outcomes might be mediated by DNA methylation (DNAm). The aim of our study is to identify the impact of PUFA intake on DNAm in the Cooperative Health Research in the Region of Augsburg (KORA) FF4 cohort and the Leiden Longevity Study (LLS). Results DNA methylation levels were measured in whole blood from the population-based KORA FF4 study (N = 1354) and LLS (N = 448), using the Illumina MethylationEPIC BeadChip and Illumina HumanMethylation450 array, respectively. We assessed associations between DNAm and intake of eight and four PUFAs in KORA and LLS, respectively. Where possible, results were meta-analyzed. Below the Bonferroni correction threshold (p < 7.17 × 10–8), we identified two differentially methylated positions (DMPs) associated with PUFA intake in the KORA study. The DMP cg19937480, annotated to gene PRDX1, was positively associated with docosahexaenoic acid (DHA) in model 1 (beta: 2.00 × 10–5, 95%CI: 1.28 × 10–5-2.73 × 10–5, P value: 6.98 × 10–8), while cg05041783, annotated to gene MARK2, was positively associated with docosapentaenoic acid (DPA) in our fully adjusted model (beta: 9.80 × 10–5, 95%CI: 6.25 × 10–5-1.33 × 10–4, P value: 6.75 × 10–8). In the meta-analysis, we identified the CpG site (cg15951061), annotated to gene CDCA7L below Bonferroni correction (1.23 × 10–7) associated with eicosapentaenoic acid (EPA) intake in model 1 (beta: 2.00 × 10–5, 95% CI: 1.27 × 10–5–2.73 × 10–5, P value = 5.99 × 10–8) and we confirmed the association of cg19937480 with DHA in both models 1 and 2 (beta: 2.07 × 10–5, 95% CI: 1.31 × 10–5–2.83 × 10–5, P value = 1.00 × 10–7 and beta: 2.19 × 10–5, 95% CI: 1.41 × 10–5–2.97 × 10–5, P value = 5.91 × 10–8 respectively). Conclusions Our study identified three CpG sites associated with PUFA intake. The mechanisms of these sites remain largely unexplored, highlighting the novelty of our findings. Further research is essential to understand the links between CpG site methylation and PUFA outcomes.